(untitled) (Práxis Educativa, 2024)
The migratory flow within the Southern Common Market (MERCOSUL) is a significant issue, and the free movement of people is one of the fundamental principles established. Even if human rights is a present theme in recent research on migratory phenomena, studies that relate the right to education and the new contours of contemporary migrations are still scarce. Thus, the objective of this study is to highlight the actions adopted by the municipality of Dourados, in the state of Mato Grosso do Sul (MS), Brazil, with regard to guaranteeing the right to education for immigrants from the MERCOSUL region. The methodological option is of a theoretical-documentary nature, with a qualitative approach. The analyzes indicate that realizing the right to education for immigrants requires a comprehensive conduct that considers several dimensions of the phenomenon, such as: guidelines, flows and protocols, mapping and identification, reception, translation and interpretation, flexibility, cultural integration projects, continued training, continuous monitoring and evaluation, support network and access to social resources. Keywords: Migratory flow. Right to education. MERCOSUL.